الشّيخ عَبد اَلكريم اَلفكون وَنهاية اَلعصر اَلوسيط - بن الشايب, محمد; جوادي, مسعود; رقيعه, سالم (جامعة الوادي - University of Eloued, 2023)
يتناول هذا البحث أحد أبرز الشخصيات الجزائرية التي عاشت نهاية الفترة الوسيطية وبداية العصر الحديث ألا وهو شيخ الاسلام عبد الكريم الفكونالقسنطيني 988ه /1073ه صاحب كتاب منشور الهداية وهو أحد أقطاب البيت الفكوني المشهور بالعلم والدين والحضوة والرئاسة حيث سلطنا الضوء على هذه الشخصية والعوامل التي ساعدت في بروزها وأبرز مؤلفاته وتلاميذه ومراسلته مع شيوخ عصره ومواقفه من أبرز القضايا التي عايشها. Summary: This research deals with one of the most prominent Algerian personalities who lived at the end of the intermediate period and the beginning of the modern era, namely Sheikh Islam Abdelkarimfakoun Constantine 988 Ah /1073 ah, the author of the book Al-Hidaya publication, one of the poles of the intellectual house famous for science, religion, Hadith and Presidency, where we shed light on this personality and the factors that helped in its emergence and highlighted his writings and students and correspondence with the elders of his ERA and his positions on the most prominent issues he experienced.
مذكرة ماستر تاريخ تخصص تاريخ الغرب الاسلامي في العصر الوسيط
Keywords: الفكون- قسنطينة – منشور الهداية; Al-fakon-Constantine-Al-Hidaya publication